Pengaruh Orientasi Kewirausahaan terhadap Kinerja Organisasi Koperasi: Orientasi Pasar sebagai Variabel Intervening (Studi pada Koperasi Primer di kota Palu, Sulawesi Tengah) - Risnawati -; Noermijati - (Jurnal Aplikasi Manajemen, 2012)
The objective of this research is to analyze the effect of entrepreneurship orientation toward market orientation and cooperation performance. The research population is primary cooperation in Palu, that include 70 primary cooperations which is still active in operation until year of 2009, with the CEO from every cooperation as a respondents. Validity and reliability of the research instrument were tested through Second Order conformatory factory analysis (CFA) and path analysis is used to test research hypothesis. Research result shows that: (1) Entrepreneurship orientation affect cooperation performance (2) Entrepreneurship orientation affect market orientation (3) market orientation affect cooperation performance (4) Entrepreneurship orientation affect cooperation performance through market orientation. The implication of this research, is how to integrate entrepreneurship orientation and market orientation as an effort to improve cooperation performance.Keywords: Entrepreneurship orientation, market orientation, cooperation performance